Alcohol misuse, drinking contexts and intimate partner violence in St. Petersburg, Russia: results from a cross-sectional study - Skochilov Roman V; Shaboltas Alla V; Zhan Weihai; Kozlov Andrei P; Krasnoselskikh Tatiana V; Abdala Nadia (BMC, 2011)
Abstract Background Alcohol misuse has been linked to intimate partner violence (IPV). However, this association is not usually examined in Russia. Moreover, more investigation is required as to whether specific drinking contexts are also associated with IPV. The objectives of this study are: to investigate whether alcohol misuse is associated with IPV and to further examine whether specific drinking contexts among drinkers are associated with IPV. Methods A questionnaire was used to collect information on demographics, health status, alcohol use, and violence involving sexual partners among 440 participants who were recruited from an STI (sexually transmitted infection) clinic center in St. Petersburg, Russia for a cross-sectional study from 2008 to 2009. Multivariate logistic regression was used for analysis. Results Overall, 47.0% participants were classified as misusing alcohol and 7.2% participants perpetrated IPV in the past three months. Participants with alcohol misuse were 3.28 times (OR: 3.28; 95% CI: 1.34-8.04) as likely as those without alcohol misuse to perpetrate IPV. Among participants who had consumed alcohol in the past three months, those who usually drank on the streets or in parks (OR: 5.62; 95% CI: 1.67-18.90) were more likely to perpetrate IPV. Conclusions Both alcohol misuse and certain drinking contexts (e.g., drinking on the streets or at parks) were associated with IPV. The association between drinking contexts and IPV needs further investigation, as do the underlying mechanisms for this association. IPV prevention initiatives might benefit from reducing alcohol misuse. Drinking contexts such as drinking on the streets or at parks as well as the factors related to the use of alcohol in these contexts may also need to be addressed.